Acute Colitis Drives Tolerance by Persistently Altering the Epithelial Barrier and Innate and Adaptive Immunity. Issue 7 (22nd February 2019) - Wardill, Hannah R; Choo, Jocelyn M; Dmochowska, Nicole; Mavrangelos, Chris; Campaniello, Melissa A; Bowen, Joanne M; Rogers, Geraint B; Hughes, Patrick A
Abstract: Background: Inflammatory bowel disease (IBD) has a remitting and relapsing disease course; however, relatively little is understood regarding how inflammatory damage in acute colitis influences the microbiota, epithelial barrier, and immune function in subsequent colitis. Methods: Mice were administered trinitrobenzene sulphonic acid (TNBS) via enema, and inflammation was assessed 2 days (d2) or 28 days (d28) later. Colitis was reactivated in some mice by re-treating at 28 days with TNBS and assessing 2 days later (d30). Epithelial responsiveness to secretagogues, microbiota composition, colonic infiltration, and immune activation was compared between all groups. Results: At day 28, the distal colon had healed, mucosa was restored, and innate immune response had subsided, but colonic transepithelial transport ( P = 0.048), regulatory T-cell (TREG ) infiltration ( P = 0.014), adherent microbiota composition ( P = 0.0081), and responsiveness of stimulated innate immune bone marrow cells ( P < 0.0001 for IL-1β) differed relative to health. Two days after subsequent instillation of TNBS (d30 mice), the effects on inflammatory damage ( P < 0.0001), paracellular permeability ( P < 0.0001), and innate immune infiltration ( P < 0.0001 for Ly6C+ Ly6G- macrophages) were reduced relative to d2 colitis. However, TREG infiltration was increased ( P < 0.0001), and the responsiveness of stimulated T cells in the mesenteric lymph nodes shifted from pro-inflammatory at d2 to immune-suppressive at d30 ( P < 0.0001 for IL-10). These effects were observed despite similar colonic microbiota composition and degradation of the mucosal layer between d2 and d30. Conclusions: Collectively, these results indicate that acute colitis chronically alters epithelial barrier function and both innate and adaptive immune responses. These effects reduce the consequences of a subsequent colitis event, warranting longitudinal studies in human IBD subjects.